Effect of different impactor designs on biomechanical behavior in the interface bone-implant: A comparative biomechanics study. (December 2020) - Bachiri, Abdessamed; Djebbar, Noureddine; Boutabout, Benali; Serier, Boualem
Highlight: The projectile shape and its velocity are two essential and determining physical parameters for predicting the behavior of the dental structure after a violent shock on the teeth. The contact areas between the bone and the implant is the seat of high concentration of equivalent stress. Conical shape projectiles are very dangerous and pose a risk to the stability of the dental structure. A conical shape projectile induces equivalent von Mises stresses in the bone and implant that are greater than those generated by a spherical projectile. Abstract: Background and Objective: The implant makes it possible to replace a missing tooth in a very esthetic way with a very comfortable result because the tooth is fixed and independent of its neighbors, like a natural tooth. Titanium alloy grade 5 or Ti-6AI-4V, has excellent properties mechanical and an interesting modulus of elasticity. It is known to be biocompatible and remains the material of choice for the medical sector: orthopedic, dental implants and maxillofacial surgery. The objective of this study was to analyze the influence on the biomechanical behavior of dental implants with a variable velocity at the implant/bone contact area and to compare the differences EQV stress between spherical and conical impactor. Methods: We chose a dental implant located in the lower jaw, in the region of the second premolar. The assembly consists of six parts: Feldsphatic porcelain crown, cobalt-chrome alloy framework, titanium alloy implant abutment and the jaw is composed of cancellous bone and cortical bone. The width and height of cortical bone model were 15.8 mm and 23.5 mm, respectively. The thickness of its upper part was 2 mm. The implant and its components were modeled using SolidWorks 2016 software and then exported to Abaqus program 6.13 using the finite element method. The geometry of the solid implant is presented in form of cylinder screw of length 8 mm and diameter 4.8 mm. The sizes of the abutment are: length l  = 7.2 mm, lower diameter d1 = 2.6 mm and great diameter d2  = 3.6 mm. Results: Maximum von Mises stress generated by spherical impactor are lower than those obtained by conical impactor. For big velocity of the impactor, the stresses may be critical since the mechanical properties of the implant material and the cortical and cancellous bone could not withstand stress magnitudes recorded in this analysis. Conclusions: A conical projectile leads to an equivalent stress greater than that generated by a spherical projectile. Whatever the projectile shape, the stress intensity increases in the different components of the dental prosthesis with increasing the impact velocity.